2019
DOI: 10.1152/physiolgenomics.00049.2018
|View full text |Cite
|
Sign up to set email alerts
|

Human genotyping and an experimental model reveal NPR-C as a possible contributor to morbidity in coarctation of the aorta

Abstract: Coarctation of the aorta (CoA) is a common congenital cardiovascular (CV) defect characterized by a stenosis of the descending thoracic aorta. Treatment exists, but many patients develop hypertension (HTN). Identifying the cause of HTN is challenging because of patient variability (e.g., age, follow-up duration, severity) and concurrent CV abnormalities. Our objective was to conduct RNA sequencing of aortic tissue from humans with CoA to identify a candidate gene for mechanistic studies of arterial dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In this study we investigated the regulation of EnNaC expression and activity after NPRC ligand binding in hAoECs. We previously showed EnNaC [29] and NPRC [30] proteins are both expressed in these cells, but this is the first investigation of a cross-talk between EnNaC and NPRC. In addition, we showed an elevation of various DAGs in hAoECs after activation of NPRC by the agonist cANF.…”
Section: Discussionmentioning
confidence: 85%
“…In this study we investigated the regulation of EnNaC expression and activity after NPRC ligand binding in hAoECs. We previously showed EnNaC [29] and NPRC [30] proteins are both expressed in these cells, but this is the first investigation of a cross-talk between EnNaC and NPRC. In addition, we showed an elevation of various DAGs in hAoECs after activation of NPRC by the agonist cANF.…”
Section: Discussionmentioning
confidence: 85%
“…The thoracic aorta simulation featured here leverages data, methods and results discussed in detail elsewhere (25,26,27,28). Briefly, the simulation focuses on coarctation of the aorta (CoA), one of the most common congenital cardiovascular defects (29).…”
Section: Resultsmentioning
confidence: 99%
“…Another genome-wide association study on human primary vascular smooth muscle cells and endothelial cells from different individuals identified that genetic variants at the NPR3 locus are associated with elevated blood pressure (27). NPR3 was found to be downregulated in human aortic sections subjected to high blood pressure from coarctation of the aorta (28), suggesting that NPR3 could be a therapeutic target for vascular disease prevention. In addition to NPR3, BDKRB2 has also been found to be involved in endothelial function and blood vessel constriction (29,30), thus determining cardiovascular health and regenerative arteriogenesis.…”
Section: Discussionmentioning
confidence: 99%